PERHITUNGAN PREMI ASURANSI MENGGUNAKAN SELECT DAN NON-SELECT TABLE PADA ASURANSI JOINT LIFE - WAHYUNI, NI LUH PUTU SRI; WIDANA, I NYOMAN; SARI, KARTIKA (E-Jurnal Matematika, 2024)
One of the basics in calculating insurance premiums is life table.  There are two types of life tables, namely select and non select table.  The purpose of the study was to calculate premiums using a select table with a two-year select period and a non-select table in term joint life insurance for 10-term insurance and endowment insurance. The select tables used are select life table with a two-year select period and non- select life table model. The result obtained is that the premium value in term joint life insurance for 10-term insurance and endowment insurance  calculated using the select table model is smaller than using the non- select table.  Beside that, it is obtained  that the difference gets bigger as the couple gets older .